Paradoxical Activation in the Cerebellum during Language fMRI in Patients with Brain Tumors: Possible Explanations Based on Neurovascular Uncoupling and Functional Reorganization - Cho, Nicholas S. (Cerebellum, 2018)
The cerebellum is known for its crossed activation pattern with the contralateral cerebral hemisphere during language functional magnetic resonance imaging (fMRI) tasks in healthy patients. Crossed cerebro-cerebellar activation has been previously shown to occur in patients with brain tumors not affecting the activation areas. However, the presence of a tumor in left Broca’s area in the inferior frontal gyrus is known to disrupt cerebral activation during language tasks. This study investigated if crossed cerebro-cerebellar activation patterns for language tasks would still occur in such patients. A total of 43 right-handed patients with a glioma affecting left Broca’s area were examined for their cerebral and cerebellar activation during an fMRI language task. Only 13 of the 43 patients exhibited crossed cerebro-cerebellar activation patterns. Statistically significant differences of atypical cerebro-cerebellar activation patterns were found between cerebral right-dominant (RD) and cerebral co-dominant (CD) (p < 0.001) as well as cerebral RD and cerebral left-dominant (LD) patients (p < 0.01), while no differences were found when patients were divided based on cerebellar dominance (p > 0.75) or tumor grade (p > 0.5). No relation was found between the cerebellar and cerebral laterality index (LI) values (ρ = −0.20; p = 0.21). Atypical activation patterns are suspected to have been caused by the tumor, perhaps a result of contralateral reorganization in some cases and false negative activation in left Broca’s area from neurovascular uncoupling (NVU) in others. Cerebellar activation may also potentially indicate cerebral false negative behavior and future cerebral contralateral reorganization.